Bad apples spoiling the metaphor? How and why self-serving leaders stir up counterproductive behaviors at work - Zhang, Yajun; Peng, Shuai; Wang, Jinsong; Akhtar, Muhammad Naseer; Wang, Yongqi (Frontiers in Psychology, 2023)
Self-serving leaders satisfy their self-interests at the cost of both employees and organizations, leading to declining organizational competitive advantage and performance. Drawing upon the Affective Events Theory (AET), we constructed and examined a theoretical model of self-serving leadership influencing counterproductive work behavior (CWB), where traditionality plays a significant moderating role through the lens of anger as a mediator. Data were collected in three waves using a survey questionnaire distributed in three industries located in the Southwest district of China. Hierarchical regression analyses were conducted on a sample of 316 employees to test the hypothesized research model. The results showed that self-serving leadership triggers employee anger, which in turn causes CWB. Furthermore, traditionality plays a significant moderating role, in which employees with higher levels of traditionality feel less anger and show less CWB. Overall, research findings have clarified how and why self-serving leadership affects employees’ emotions (such as anger) and behavior (such as CWB), bringing new insights into the self-serving leadership and employee behavior literature. Research implications on the management of self-serving leadership, limitations, and future recommendations of research are also discussed.